Mindful Learning: Mindfulness Practice Matters for Students on the Quality of Learning in the Classroom - Santi Santi; Ayu Andriyaningsih; Wistina Seneru; Burmansah Burmansah; Luwiha Luwiha; Arya Sura Pratama; Juni Suryanadi (Universitas Sebelas Maret, 2024)
This study aimed to find the effect of mindfulness practices on the quality of junior high school students' learning. The problems that occur in students are that students pay less attention when the teacher explains the material, can understand the material if the lesson is following their interests, some teachers are also considered to use teaching methods that are not very suitable for students, and some teachers are considered too monotonous in teaching students are also often sleepy in class during learning. This study uses a quantitative approach with a survey method. The population in this study was 70. This study was conducted in junior high schools with respondents from the 2023/2024 academic year. The study's results showed a significant favorable influence between mindfulness practices and the quality of student learning, with a t count of 13.706 and a significance value (p) of 0.000 <0.05. From the simple regression analysis calculation results, the R square value was obtained as 0.734, meaning that mindfulness practices affect the quality of learning by 73.4%, and the remaining 26.8% is influenced by other factors not discussed in this study.